(3GdEHGfI GdeMceI aj GdCSeGA GdeHgeIs - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdaVd GdbQTi bGd MOKfG GdNWjH bGd GdMeO ddg GdgfG hehdGfG s
(3BNQgG (B:s
(3jfJgi HMOjK (B: (3Yf YGFTI CfgG GQGOJ Cf JTJQi LGQjI JYJbgG abGd CgdgG (B: (3fHjYgG Ydi Cf hdGAgG dfG s
(3GdfSNI HgG MhGTs
(3YdjgG SeGYGJ HYVgG SfI (B669s
(3GdeNWhW QhGjg CHj GdaJM fUQ Gddg Hf eMeO Hf YHO Gdbhis
(3QhGjI CHj GdaVd CMeO Hf eMeO Hf gHI Gddg GdbQTi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
Keywords: (3GdJGQjNs